Assessing The Students’ Translation Quality: Evidence From Nahdlatul Ulama University of Purwokerto - Naeli Rosyidah; Rahmah Diani Eliyanti; Ade Christanty Yudha Bestari (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2026)
Translation quality is an essential aspect to ensure that the message is accurately transferred and easily understood. Nonetheless, there are still discrepancies in the pupils' translation performance, which calls for more investigation. Thus, the purpose of this study is to evaluate the students' accuracy, readability, and acceptability when translating texts from English into Indonesian. Using a descriptive quantitative methodology, the study was carried out with students from Nahdlatul Ulama University of Purwokerto's English Education Study Program. The three components of translation quality were measured by analyzing the data from the students' translation assignments using a scoring rubric. This study used document analysis assessing 10 students' translation products. The findings indicate that the students' translation quality is categorized good. The results show that pupils generally perform well while translating. Readability had the highest average score (2.82), followed by accuracy (2.58) and acceptability (2.61), suggesting that the majority of students can produce translations that are understandable and straightforward. The lower accuracy and acceptability scores, however, indicate that some students may still struggle to preserve semantic equivalency and generate natural statements in the target language